2012
DOI: 10.2463/mrms.11.265
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Measurement of Longitudinal Relaxation Time of Human Blood by Inversion-recovery Fast Gradient-echo MR Imaging at 3T

Abstract: Purpose: Accurate longitudinal relaxation time (T 1 ) of arterial blood is important in evaluating blood ‰ow in tissue by arterial spin labeling magnetic resonance (MR) imaging. Few studies have reported the T 1 of human arterial blood in vivo, especially using 3-tesla MR imaging. T 1 values of human venous blood in vivo have been reported, but they diŠer from those measured in vitro. We aimed to evaluate the accurate T 1 of human arterial blood in vivo.Methods: We measured T 1 values of blood in 10 healthy vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
7
27
0
Order By: Relevance
“…a). As demonstrated in previous studies on both arterial and venous blood, the blood relaxation rate 1/T 1 has a linear dependence on Hct. Earlier work has asserted hemoglobin as the main source of the T 1 relaxation in arterial blood.…”
Section: Discussionsupporting
confidence: 69%
“…a). As demonstrated in previous studies on both arterial and venous blood, the blood relaxation rate 1/T 1 has a linear dependence on Hct. Earlier work has asserted hemoglobin as the main source of the T 1 relaxation in arterial blood.…”
Section: Discussionsupporting
confidence: 69%
“…Nevertheless, in the LV blood pool, the mean T 1 measured with MRF over all volunteers was 1807ms (min 1701ms, max 1931ms) and the mean T 2 was 91ms (min 76ms, max 107ms). The blood T 1 measurements are in agreement with literature values of 1550-1932ms (40)(41)(42)(43); however, the blood T 2 measurements obtained with both MRF and T 2 -prepared bSSFP are lower than in previously reported studies, which found T 2 values in oxygenated blood of 175ms (44) to 275ms (40).…”
Section: Human Volunteer Imagingsupporting
confidence: 79%
“…T1 values of blood may be influenced by Hct, temperature, pH, and oxygenation levels. 9,[15][16][17][18][19] In fact, accurate measurements of human blood T1 values are an important topic in itself because these values are an important MR parameter for quantitative physiological and functional MR measurements, such as arterial spin labeling with cerebral blood volume calculations. Previously, T1 values of bovine blood had been measured at 1.5 T, 3 T, 18 4.7 T, 7 T, and 9.4 T. 17 T1 values of rat blood have also been measured at 11.7 T. 16 Human blood T1 values have also recently been measured at 3 T 19 and 7 T.…”
Section: Discussionmentioning
confidence: 99%
“…However, conflicting conclusions regarding the influence of blood oxygen content have been reached in previous studies. [15][16][17][18][19] In the study of Lin et al, 16 rat blood T1 values were found to be independent of oxygenation. The study of Rane et al 15 demonstrated that T1 values of human blood at 7 T differed depending on whether arterial or venous blood was examined.…”
mentioning
confidence: 96%